Anomalous Facial Nerve: An Unusual Cause of Obstruction of Middle Ear Ventilation - Das, S; Tuli, IP (Kathmandu University Medical Journal, 2015)
Numerous anomalies and variations of facial nerve anatomy leading to iatrogenic injury are described. However, there are no reports of facial nerve dehiscence near its second genu causing a hump and obstructing middle ear ventilation pathway, as found in our case.This particular anomaly of facial nerve is being reported to highlight its uniqueness and that a dehiscent facial nerve may be a rare but dangerous cause of obstruction of the attic ventilation. One has to be aware of this unusual anomaly to prevent inadvertent damage to the facial nerve while clearing aditus block in persistent otitis media.Kathmandu University Medical Journal Vol.13(1) 2015; 74-76